CARBONIFEROUS 40Ar/39Ar AGE OF THE RARE METAL-ENRICHED RHYOLITES AND IGNIMBRITES IN THE SAKMARA ALLOCHTHON OF THE SOUTHERN URALS, THEIR GEOCHEMICAL FEATURES AND GEODYNAMIC SETTING - A. V. Ryazantsev; A. V. Pilitsina; I. A. Novikov; K. E. Degtyarev (Известия высших учебных заведений: Геология и разведка)
In the structure of the Sakmara allochthon of the Southern Uralssequence with rhyolites and ignimbrites locally occures. They have Nb-Zr-REE geochemical specialization. This sequence unconformably overlays folded Paleozoic complexes, including the Devonian ones. Rhyolite contains K-feldspar and quartz phenocrysts, K-feldspar glomeroporphyrites and granite xenolith. Geochemical features of the rhyolites show intraplate-originated affinities and A-type granite composition. 40Ar/39Ar age of the felsitic matrix of the rhyolites of 303±2 Ma defines the age of the volcanic complex origin. For feldspar phenocrysts the age of 306±3 Ma and 337±3 Ma is obtained. The first value coincides to the matrix age and connected with formation of the volcanic complex. The second value belongs, apparently, to xenogenic material. Obtained age values reflect the evolution of Carboniferous active continental margin magmatism, widespread in different structural zones of the Urals. Rare-metal rhyolites characterize the final late Carboniferous intraplate (rift-related) back-arc magmatism at the active continental margin. Volcanism preceded to a collision-related ophiolitic thrust nappes emplacement.